Relationships of Egg Size of Clarias Gariepinus on Fertilization, Hatching and Frys Survival Rates - Adams, Azubuike (Journal of Biotechnological Research, 2016)
Eggs from matured female brood stocks were obtained and classified into 3 egg size classes, large, medium and small based on the size of eggs. 1.0-1.2mm, 0.5-0.9mm and 0.3-0.5mm respectively. They were fertilized with milt obtained from sacrificed males. The data obtained was used to assess the fertilization, hatching and frys survival rates of Clariasgariepinus. The result shows that the size of egg has a significant effect on the fertilization, hatching and fry survival rates of Clariasgariepinuus. That is the bigger the egg size the higher the fertilization, hatching and frys survival rates and vice versa. The physic-chemical parameter (ie the temperature PH and dissolved oxygen) values are within the expected range.